Prediction of robust stability boundaries for milling operations with extended multi-frequency solution and structured singular values. (December 2017) - Hajdu, David; Insperger, Tamas; Bachrathy, Daniel; Stepan, Gabor
Abstract: Reliable prediction of machine tool chatter is an essential problem in efficiency-oriented machine tool centers, since it requires the precise characterization of the dynamics of the machine-tool-workpiece system and the cutting force characteristics. Due to imperfect measurements, noise, uncertain and varying operational conditions, the mathematical models provide a deficient representation of the system. This leads to the need for the adaptation of robust stability analysis methods, which guarantee stability against bounded uncertainties and perturbations. In this paper, a frequency-domain approach is presented to calculate the robust stability boundaries of chatter-free machining parameters for milling operations. The idea is based on the concept of the stability radius and structured singular values, which is combined with the extended multi frequency solution. The proposed method is tested in a real case study.